The sword is represented in the poetry system of Al-Mutnabi - Al - Isse, Sultan Atef (Arab Journal for Sciences and Research Publishing, 2018)
Deals with the subject of the sword in the poetry of Al-Mutnabi by studying the poetic presence of this thing in his poetry.The problem of research is how Al-Mutanabi uses the stylistic mechanisms and tools of the sword system and the relationship of this system to its cultural system and its presence in the creative self of Al-Mutanabi.The research deals with the limits of the methodological method, how to use it in the text of poetry of Al-Mutanabi, the sword emerges in the system Mutanabi poetry has a close relationship with the cultural system, the sword is an external component, In a certain stage in his poetry does not exceed in his symbolism and his main function (appeal), and then turn the sword in a second stage to glowing and explosive symbolism, embodying the fusion of Mutanabi poetic in the sword , Al- Mutanabi 's tendency to intensify metaphors, focusing on conflicting dynasties, then moves on to another stage in which the sword tends towards transformation and alienation, where the symbolism of the sword is embodied in the frustrated Mutanabi,The sword moves from the physical symbol to the spiritual, indicating the success of Mutanabi in the use of the sword as a cultural symbol, compatible with the same Arab individual, and its cultural system,Based on this study, there is a need for the monetary arena, for research that shows the bright themes of the Arab heritage through the poetry of poets such as: (The Palm, the tent, the camel, the Kaaba).
Keywords: Al-Mutanabbi; the sword; poetry; representation; system